PROTEKSI BERUPA TECHNICAL BARRIER OLEH AMERIKA TERHADAP CPO INDONESIA YANG MERUPAKAN PELANGGARAN DALAM PRINSIP TBT AGREEMENT-WTO - , HILMAN RAMADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
International trade under WTOâs modality is a multidiciplinary course. This matter is highly crucial for Indonesian interest as developing country. Therefore, we extremely rely on international trade. Since the day one Indonesia ratified WTO establishment, Indonesia had several lawsuit before WTO Dispute Settlement Body (DSB-WTO) either as a plaintiff or a defendant. Thus, it is indispensable for Indonesia to consduct research over international trade system and to master it as a whole. As an internee, as well as potential paralegal who is interested in legal research, getting into UGM think tank research to assist and conduct research and the like are overly interesting for me. Hopefully, it could be invaluable experience for my future career in legal research. Additionally, there is an opportunity pursuant to Rectoral Decree No.3/P/SK/HT/2013, it firmly stated that, D3 is minimum requirement for researcher at UGM center studies institution. The topic which Author arised is CPO as a major Indonesian export commodity to all over the world , notably to European union (EU) , China and the United States (USA), as we have comparative advantages compared to similar oil product (Vegetable Oil). yet lately , there are concern among diverse states, particularly USA aginst indonesian CPO and subsequently they banned it through various issues ranging from healthy and even masquerating environmental issue to justify its action. By Passing the regulations that prohibit importation, unless the ones that have prescribed by WTO provisions previously, which led to the technical barrier on exports of other countries. In this sense, it obviously violates the fundamental WTO principles to get rid the technical barrier itself in international trade. Hence, here the author is seeking to unveil it as my internship output at the PSPD which had been studied previously by CWTS researchrers in legal cluster as a real contribution to advocating Indonesian trading interests on internasional level.